Cognitive assessment development: item analysis with classical and modern theories - Desi Putriani; Riza Dhifa Alzabarjud Putra; Karlina Anjani; Yurizka Melia Sari (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Understanding geometric concepts, particularly angles in circles, is fundamental in junior high school mathematics and is crucial in enhancing students' higher-order thinking skills. Assessing students’ cognitive understanding requires valid and reliable instruments that align with curriculum standards and student abilities. This study aims to construct and characterise a cognitive test instrument on angle material in circles through item analysis using Classical Test Theory with Microsoft Excel and Modern Test Theory with RStudio. A mixed-methods approach combining qualitative and quantitative techniques was used to collect data through observation and item analysis. The test instrument consists of five items to measure students’ understanding and analytical abilities. Content validation using the Aiken formula yielded an Aiken index of 1 for each item, indicating all items were valid. Classical analysis showed that items 1 and 3 were difficult, while items 2, 4, and 5 were of medium difficulty. Using the Partial Credit Model (PCM), all items fell within the medium-hard difficulty range. Power differential analysis revealed that item 3 was poorly constructed and should be removed. The results demonstrate that the developed instrument is valid and can differentiate levels of student understanding. This test is expected to support efforts to improve mathematics learning and better prepare students for numeracy literacy components in the Minimum Competency Assessment (MCA). The instrument also provides a framework for developing similar tools in other areas of mathematics education to enhance the accuracy of student learning evaluations.